Growth and photosynthetic development of Swietenia mahagoni in substrates inoculated with arbuscular mycorrhizal fungi - Falcón Oconor, Emir; Cobas López, Milagros; Bonilla Vichot, Marta; Rodríguez Leyva, Orfelina (Bosque (Valdivia), 2023)
Inoculation with arbuscular mycorrhizal fungi (AMF) has allowed for controlled development and growth in different species. However, its effect on some tropical species such as Swietenia mahagoni has not been evaluated. This study evaluated the growth and photosynthetic development of S. mahagoni produced in substrates inoculated with AMF. Using a completely randomized design, the combinations of two factors were evaluated: substrate (cocoa husk + coconut fiber + composted pine sawdust in proportions 6:2:2 and 2:6:2, and a control composed of soil + cocoa husks in a 9:1 ratio) and mycorrhizal strains (Glomus cubense, Rhizoglomus irregulare and Funneliformis mosseae). From 30 to 120 days after the seed’s germination in the nursery, the leaf surface and the total dry mass were evaluated, and growth analysis was carried out using the relative growth rate and the net assimilation rate. At 120 days, the photosynthetic rate, stomatal conductance, transpiration and internal CO2 concentration were evaluated. Significant interactions between the different factors were found for all the variables evaluated. The Glomus cubense and Rhizophagus intraradices strains, in the substrate made up of 20 % cocoa husk + 60 % coconut fiber + 20 % sawdust, produced significant increases in the growth and photosynthetic development of S. mahagoni. The importance of the mycorrhizal association is evident, as it provides S. mahagoni seedlings with more efficient photosynthetic mechanisms, improving their establishment in plantations.